Classification and assessment of effective dormancy breaking methods for oil palm (Elaeis guineensis Jacq.) seeds - Ghazali, Mohd Norsazwan (2016)
Oil palm seeds require more than six months to germinate under natural condition.Commercial seed producers have adopted heat treatment to break oil palm seed dormancy. However, no particular studies have been conducted to systematically determine and classify oil palm seed dormancy type. In the first experiment, different method to evaluate dormancy type were conducted on T × T (tenera × tenera) and D × P (dura × pisifera) seeds. This includes physical,morphological and physiological dormancy tests. Physical dormancy tests included imbibition of intact (control), chemical (soaking with 98% sulphuric acid for two minutes) and mechanically scarified (fibre plug removal and puncturing testa layer by using steel probe), as well as heat treated (40C treatment for 50 days) seeds to determine percentage of mass increase over time. Morphological dormancy characteristics were evaluated by storing the seeds at room temperature for 32 weeks to monitor embryo growth (length and width) as well as the resulting germination percentage. The effects of heat treatments were also studied by incorporating 30 days heat treatment, 50 days heat treatment or control (no heat treatment) before measuring the embryo growth and germination percentage. Physiological dormancy was evaluated by pre-soaking the seeds in 150 mg L-1 GA3 (gibberellic acid) and monitoring germination at room temperature or 30°C condition. Results indicated that the seeds were unable to imbibe water, regardless of scarification treatments. This suggests that oil palm seeds exhibit physical dormancy characteristics. Morphological tests on seeds at room temperature indicated that an embryo length of 3.64 or 3.03 mm was required to initiate germination in T × T and D × P seeds, respectively. The applications of heat treatments (40°C) were able to accelerate embryo growth, regardless of treatment duration. On the other hand, application of exogenous GA3 did not significantly increase germination during physiological dormancy test. The results indicate that oil palm seed exhibits combination of physical, morphological and physiological dormancy type. In the second experiment, alternative methods to break oil palm seed dormancy of T × T, D × P EBOR and D × P ELMINA were evaluated based on dormancy type determined from the first experiment. This include adoption of higher temperature treatment (50°C), alternating temperature regimes of high (40°C) and low (7°C) for different duration; as well as combining alternating temperature regimes of high (40°C) and low (7°C) temperatures with growth hormone GA3 during germination period. The seeds were then allowed to germinate for 60 days. Parameters evaluated include percentage of normal pre-germinated seeds, percentage abnormalities, percentage of diseased seeds and Coefficient Velocity of Germination. The results indicated that adoption of alternating temperature along with exogenous GA3 application during germination were able to result in similar percentage of normal pre-germinated seeds as the commercially practiced method, with acceptable percentage abnormalities and diseases occurrence level. . It was found also that the germination temperature should be less than 50°C due to higher abnormalities of germinated seeds as seen in the developing radicle and plumule. Cycles of alternating temperature was found to accelerate embryo growth prior to germination as it potentially alters the overall hormonal balance particularly leading to reduction of ABA (abscisic acid) and higher production of GA hormone during germination. This study suggests that there are alternative methods that can be adopted to break oil palm seed dormancy based on prior understanding of the exact dormancy type underlying the seeds.